1998
DOI: 10.1159/000014984
|View full text |Cite
|
Sign up to set email alerts
|

X-linked sex-reversing genes

Abstract: Rearrangement of the X chromosome generates fertile XY females in the wood lemming, and a duplication has been discovered in Xp21 in some XY females in the human. This has enabled identification and mapping of a novel sex-reversing gene in the human, double dosage of which blocks development of the testis. Whether or not the human gene is related to the gene that causes sex reversal in the wood lemming remains to be seen. Yet similar genes must exist in all eutherian mammals, according to Ohno’s Law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Duplication of the DSS (dosage-sensitive sex reversal) gene at Xp21.3, causes female development in XY fetuses with an intact SRY gene [Bardoni et al, 1994;Wachtel, 1998] Although the precise sexreversing lesion is not identified in the XY woman that we tested, it is clear that the SRY gene is present in her cells and that it is Y-situated. Further study with the PRINS method might help us to determine whether DSS is duplicated in this patient.…”
Section: Discussionmentioning
confidence: 93%
“…Duplication of the DSS (dosage-sensitive sex reversal) gene at Xp21.3, causes female development in XY fetuses with an intact SRY gene [Bardoni et al, 1994;Wachtel, 1998] Although the precise sexreversing lesion is not identified in the XY woman that we tested, it is clear that the SRY gene is present in her cells and that it is Y-situated. Further study with the PRINS method might help us to determine whether DSS is duplicated in this patient.…”
Section: Discussionmentioning
confidence: 93%
“…In the Scandinavian wood lemming (Myopus schisticolor), a great excess of females (four females to one male) arises on the basis of an X-linked gene that suppresses the action of the X-linked testis-determining gene, producing fertile XY females mating with XY males [Wachtel, 1998]. The 50% expected zygotic lethality due to heterogamety of both sexes is avoided through a cumbersome mechanism of mosaicism, with males beginning life XY, but then loosing the X preferentially in the male germ line so that all females begin life as XO.…”
Section: Sex Determinationmentioning
confidence: 99%
“…During oogenesis, nondisjunction restores two Xs. In the Scandinavian wood lemming (Myopus schisticolor), a great excess of females (four females to one male) arises on the basis of an X-linked gene that suppresses the action of the X-linked testis-determining gene, producing fertile XY females mating with XY males [Wachtel, 1998]. In this species the hazard of zygotic lethality is avoided by eliminating the Y from the female germ line and reconstituting an XX chromosome constitution by nondisjunction.…”
Section: Sex Determinationmentioning
confidence: 99%